Stereoselective Halogenation in Natural Product Synthesis - Chung, Won-jin; Vanderwal, Christopher D. (Angewandte Chemie International Edition, 2016)
At last count, nearly 5000 halogenated natural products have been discovered. In approximately half of these compounds, the carbon atom to which the halogen is bound is sp3‐hybridized; therefore, there are an enormous number of natural products for which stereocontrolled halogenation must be a critical component of any synthesis strategy. In this Review, we critically discuss the methods and strategies used for stereoselective introduction of halogen atoms in the context of natural product synthesis. Using the successes of the past, we also attempt to identify gaps in our synthesis technology that would aid the synthesis of halogenated natural products, as well as existing methods that have not yet seen application in complex molecule synthesis. The chemistry described herein demonstrates yet again how natural products continue to provide the inspiration for critical advances in chemical synthesis. With thousands of natural products containing halogen‐bearing stereogenic centers, a wealth of methods have been developed for their stereocontrolled introduction in the context of total synthesis. This Review highlights the creative ways in which organic chemists have dealt with the challenges of stereochemically rich, halogenated natural products.